Seed, soil and mechanical transmission of viruses causing maize lethal necrosis in maize - Gatunzi, F.K.; Miano, W.D.; Mukunya, D.; Atwok, Luka; Ngaboyisonga, Claver; Mahabaleswara, Suresh L. (Indian Society of Mycology and Plant Pathology, 2022)
Reduction in production and yields of cereal-based foodstuffs, particularly maize has resulted in increase in importation of maize in most Sub-Saharan countries. Interactions of viruses causing Maize lethal necrosis (MLN) disease in Eastern Africa have been reported to occur between Maize chlorotic mottle virus (MCMV) and (SCMV) and this Synergy was reported since the beginning of the Sugarcane mosaic virus 19 century. Previous studies on seed and soil transmission of the two viruses have not been conclusive. th This study aimed at investigating the effect of mechanical transmission and seed and soil transmission of viruses causing MLN disease. Three experiments were set concomitantly and separately in the greenhouse at KALRO-CIMMYT Naivasha MLN screening facility-Kenya. They were laid out in a completely randomized design (CRD) with three replications each. Certified seeds were sourced from CIMMYTKiboko research center and clean soil was collected from Aberdare range forest and steam sterilized. All plants were evaluated for incidence, severity, and tested with ELISA. Certified maize seeds grown in steam sterilized forest soil in greenhouse showed that there were no typical and visible symptoms of virus diseases in the plants of both seed and soil experiments. However, ELISA results confirmed presence of MCMV both in seed and soil experiments at the rate of 4.17 and 8.34 per cent respectively. SCMV transmission by seed or through soil could not be confirmed by ELISA test. Based on these findings, it can be concluded that MCMV is transmitted through infected seed and contaminated soils though at low rates and becomes the major virus in the mechanism of the transmission; while SCMV was not. Mechanical infection can play a major role in MLN in disease development, though it is rare in natural conditions. These findings are important to maize growers in that they may prevent secondary infection in the field and reduce MLN incidence and severity using resistant genotypes and minimizing mechanical transmissions.